STYLISTIC DEVICES IN ENGLISH LITERARY TEXTS AND THEIR FUNCTIONS - Abdulhamidova Gulzoda; G'ofurova S. M. (TADQIQOTLAR, 2026)
Annotation: This article explores the various stylistic devices employed in English literary texts and their multifaceted functions. By analyzing examples from different genres, it aims to elucidate how these devices enhance meaning, evoke emotions, and contribute to the overall aesthetic experience of literature.